Return Policies and Everyday Resistance: An Exploration of Nigerian Migrants’ Experiences in Austria - Simona Schreier (sozialpolitik.ch, 2023)
This article delves into the nuances of resistance among Nigerian migrants in Austria, situated within the larger framework of European migration. Against the backdrop of the stringent migration regulations implemented in Austria during the 2015 long summer of migration and amplified during the COVID-19 pandemic, this study aims to provide a deeper exploration of the political sociology of return. Drawing on semi-structured interviews conducted with 18 Nigerian migrants, I examine the perspectives of migrants and their interpretations of voluntary and forced return policies and implementation, shedding light on their motivations, strategies, and decision-making processes. Additionally, the paper incorporates 15 interviews with government officials, non-governmental organisations, and activists to explore the implementation of return policy. Using the framework of everyday resistance by Johansson and Vinthagen (2019), this study uncovers the nuanced ways in which Nigerian migrants in Austria navigate the pressures of returning to their home countries. This analysis is especially significant because of Nigeria’s prominence as a major origin country for migrants in Europe. It provides valuable insights into the broader European migration context and contributes to a better understanding of resistance within return migration processes. These acts manifest in various forms in everyday life, challenging the execution of asylum and return policies in specific physical locations, such as workplaces, cities, and streets, highlighting the complex subtleties of resistance in the context of return migration management.